Impact of telmisartan on cardiovascular outcome in hypertensive patients at high risk: a Telmisartan Randomised AssessmeNt Study in ACE iNtolerant subjects with cardiovascular Disease subanalysis - Foulquier, Sebastien; Boehm, Michael; Schmieder, Roland; Sleight, Peter; Teo, Koon; Yusuf, Salim; Schumacher, Helmut; Unger, Thomas (Journal of Hypertension, 2014)
In the Telmisartan Randomised AssessmeNt Study in ACE iNtolerant subjects with cardiovascular Disease, all patients were at high cardiovascular risk, and a substantial proportion were hypertensive. We performed a post-hoc analysis to explore the hypothesis that telmisartan has a differential action in hypertensive vs. nonhypertensive patients.The primary four-fold endpoint (composite of cardiovascular death, myocardial infarction (MI), stroke, or hospitalization for heart failure), the secondary three-fold endpoint (cardiovascular death, MI, and stroke), the individual components, new onset of left ventricular hypertrophy (LVH), and new onset of albuminuria were analyzed.There was no evidence for a significantly differential treatment effect of telmisartan in hypertensive and nonhypertensive patients for any endpoints, although the occurrence of the secondary three-fold endpoint was significantly lower in the telmisartan group (13.0%) compared with placebo (15.0%, P < 0.05) only in hypertensive patients. Moreover, data from this post-hoc analysis suggest that MI may be less frequent in hypertensive patients treated with telmisartan (3.8 vs. 5.1%; P < 0.05). Telmisartan may also reduce new onset of LVH (nonhypertensive patients P < 0.05; hypertensive patients P < 0.001) in both subgroups, and new onset of microalbuminuria and macroalbuminuria in hypertensive patients (P < 0.001 and P < 0.01, respectively).The effect of telmisartan in hypertensive and nonhypertensive patients at high cardiovascular risk was not different. This post-hoc analysis suggests that MI may be further reduced by telmisartan in hypertensive patients. Further investigations are needed to study the hypotheses raised by this explanatory analysis.
EVALuna2:3708